"The Impact of the Spread of the Arabic Language on Non-Native Speakers in Africa: Between the Challenges of Reality and the Prospects for the Future (Chad as a Case Study)" - Othman Jabara Taqal, Bakhit (El Omda in Linguistics and Discourse Analysis, 2018)
Arabic is one of the oldest and most deeply rooted languages in Africa, and its spread has been closely intertwined with Islam; wherever Islam reached, the Arabic language accompanied it. The connection between the Republic of Chad and the Arabic language is largely shaped by its geographical location at the heart of the African continent. By virtue of this position, Chad served as a crossroads for trans-Saharan trade routes linking the eastern and western parts of Africa. As a result, it witnessed extensive waves of migration, particularly Arab migrations arriving from the Nile Valley in the east and from the Maghreb in the north, carrying with them Islam and the Arabic language. This study, entitled “The Impact of the Spread of the Arabic Language among Non-Native Speakers in Africa: Between Present Challenges and Future Prospects – Chad as a Model,” is structured into several sections, followed by a conclusion presenting the main findings and recommendations, along with a list of sources and references